An Analysis of Code Mixing Used by Raymond Chin on Merry Riana Youtube Chanel - Luh Sintia Herianti; I Gusti Ayu Vina Widiadnya Putri (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
This study aimed to identify the types and meaning of code mixing used by Raymond Chin in Merry Riana youtube channel entitled “Muda, Pintar, Kaya, Ternyata Ini Sisi Lain Raymon Friends Of Merry Riana”.This study used descriptive qualitative method for analysis the data. Several techniques were used to collect the data. The first step,the writer downloading the video from Merry Riana YouTube channel, second, the writer watching and listening the video with carefully and repeatedly,third,transcribing the conversation into text, fourth, finding the code mixing found in the video, and finally, the researcher classify the categories of code mixing based on the theory from Muysken (2000). Based on the analysis, this study found the total frequency of code mixing used by Raymond Chin is 176, with 80 from insertion code mixing, 79 from alternation code mixing, and 17 from congruent lexicalization code mixing. The type of code mixing that is most widely used by Raymond Chin in Mery Riana YouTube channel entitled “Muda,Pintar, Kaya ,Ternyata Ini Sisi Lain Raymon|Friends Of Merry Riana” is insertion code mixing. In addition, the reason of code mixing Talking About a Particular Topic in 94 utterance following by Intention of Clarifying the Speech Content For Interlocutors with 82 occurrences. Keywords: Code Mixing; Sociolingistic; Youtube Channel